Alleviating writing anxiety through Artificial Intelligence: a digital shift in global education - Mohd Ali, Siti Nur Dina; Ismail, Mohd Hafizul (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The introduction of artificial intelligence (AI) in digital education has brought about a transformative shift in how writing is taught and experienced worldwide. Writing is indeed tough and challenging for students as they need to put effort into using grammatically correct sentences and organising the ideas with sound judgment (Shen et al., 2024). As institutions strive to equip students with 21st-century skills, the adoption of generative AI-powered tools is garnering interest around the globe, raising a growing concern about how these technologies can support students in overcoming the fear associated with academic writing. To what extent does AI allow students to overcome their writing anxiety? Writing anxiety is a prevalent issue, especially among students for whom English is a second or foreign language. L2 students’ writing anxiety is significantly influenced by how they measure their own anxiety for the target language (Ali & Ismail, 2021). As the writing process itself involves complex sentence structures, students must put effort into their writing. Fear of judgment and a lack of confidence, coupled with linguistic insecurity, often inhibit students from expressing themselves in writing. The efforts invested in writing reflect the students’ cognitive process of conveying their thoughts into words (Hayes, 2000). However, AI-based writing assistants such as Grammarly, QuillBot, and ChatGPT, to name a few, are changing this narrative. These tools provide real-time grammar correction, vocabulary suggestions, and idea-generation support, enabling students to build fluency and reduce the cognitive load associated with drafting.